2010
DOI: 10.1007/s10067-010-1522-3
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between synovitis detected on enhanced-magnetic resonance imaging and a histological analysis with a patient-oriented outcome measure for Japanese patients with end-stage knee osteoarthritis receiving joint replacement surgery

Abstract: Osteoarthritis (OA) is a disease that primarily results in the degeneration and destruction of the articular cartilage. However, synovitis that occurs secondarily by this primary phenomenon is crucial for both the structural and symptomatic progression of the disease. The Japanese Knee Osteoarthritis Measure (JKOM) was created as an outcome measure for Japanese patients with knee OA. This study was conducted to determine whether synovitis in knee OA correlates with the current disability of patients with knee … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 20 publications
2
39
0
1
Order By: Relevance
“…In synovitis, the synovial membrane produces proteases and cytokines, which enhance cartilage degradation. In addition, while synovitis occurs throughout the affected joint in rheumatic arthritis, synovitis occurs locally and more mildly in OA (Ayral et al, 2005; Goldring and Goldring, 2007; Liu et al, 2010; Ning et al, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…In synovitis, the synovial membrane produces proteases and cytokines, which enhance cartilage degradation. In addition, while synovitis occurs throughout the affected joint in rheumatic arthritis, synovitis occurs locally and more mildly in OA (Ayral et al, 2005; Goldring and Goldring, 2007; Liu et al, 2010; Ning et al, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…Total assessment scores range from 0 points (best) to 100 points (worst). A previous study confirmed the superiority of the JKOM scale for evaluating the disability of Japanese patients with knee OA compared with the WOMAC and VAS pain scales [11].…”
Section: Self-reported Knee Functionmentioning
confidence: 77%
“…13), we also showed that synovitis is associated with symptoms in advanced-to endstage knee OA [53]. We examined whether synovitis in knee OA assessed by histological examinations and enhanced MRI correlated with the disability of patients with end-stage knee OA who underwent joint replacement surgery.…”
Section: Early-to Middle-stage Knee Oamentioning
confidence: 98%
“…The expression levels of TGF-b in the sublining layer of the medial perimeniscal synovial tissue in the patients Table 7 Correlation between the total histological synovitis score (HSS) and the whole-organ magnetic resonance imaging score (WORMS) in patients with end-stage knee OA receiving TKA [55] MRI-detected OA pathologies HSS Fig. 14 A simple regression analysis comparing the histological and enhanced MRIevaluated synovitis score with the JKOM score in patients with end-stage knee OA [53]. MRI magnetic resonance imaging, ROI region of interest, JKOM Japanese Knee Osteoarthritis Measure.…”
Section: Early-to Middle-stage Knee Oamentioning
confidence: 99%